2015
DOI: 10.1155/2015/479318
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transitions of Binary Lipid Mixtures: A Combined Study by Adiabatic Scanning Calorimetry and Quartz Crystal Microbalance with Dissipation Monitoring

Abstract: The phase transitions of binary lipid mixtures are studied by a combination of Peltier-element-based adiabatic scanning calorimetry (pASC) and quartz crystal microbalance with dissipation monitoring (QCM-D). pASC, a novel type of calorimeter, provides valuable and unambiguous information on the heat capacity and the enthalpy, whereas QCM-D is proposed as a genuine way of determining phase diagrams by analysing the temperature dependence of the viscosity. Two binary mixtures of phospholipids with the same polar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 48 publications
7
22
0
Order By: Relevance
“…At relatively lower T (or higher T m ) s o is evidenced to exist as a macroscopic phase separated state via fluorescence experiments, AFM, and NMR. s o can disappear at physiological temperatures due to presence of Chol (11,(48)(49)(50)(51) or unsaturated lipids, (52)(53)(54)(55) which lower the T m of saturated lipids. At high (≳40 mol%) Chol concentrations macroscopic phase separations disappear.…”
Section: Tous(2)mentioning
confidence: 99%
See 1 more Smart Citation
“…At relatively lower T (or higher T m ) s o is evidenced to exist as a macroscopic phase separated state via fluorescence experiments, AFM, and NMR. s o can disappear at physiological temperatures due to presence of Chol (11,(48)(49)(50)(51) or unsaturated lipids, (52)(53)(54)(55) which lower the T m of saturated lipids. At high (≳40 mol%) Chol concentrations macroscopic phase separations disappear.…”
Section: Tous(2)mentioning
confidence: 99%
“…The impact of Chol concentration on the structure and dynamics associated with liquid phase behavior in lipid bilayers was investigated using a CG ternary lipid mixture observed to achieve macroscopic phase separation in molecular dynamics simulation. Simulations of DPPC, DIPC, and Chol lipids at 0, 3,7,13,22,30,42,53, and 61 mol% Chol, maintaining DPPC and DIPC at equimolar ratios, were performed. Three 11 µs replicate trajectories of each system were sampled representing a total of 3 x 9 x 11 µs = 297 µs of simulation.…”
Section: A Spatial and Structural Equilibrationmentioning
confidence: 99%
“…Although not specified on the current data sheet [33], older versions mention that this material is a mixture of alkanes. It is described as a solidliquid PCM with a melting region of [38][39][40][41][42][43] C, and it stores 174 kJ kg À1 between 35 and 50°C. Three samples were prepared.…”
Section: Experimental Details Rt42 Samplesmentioning
confidence: 99%
“…novel Peltier-element-based adiabatic scanning calorimeter (pASC), which provides greater user-friendliness and also allows smaller samples [31,32,37,38]. At the core of the pASC, as can be seen in the schematic depiction in Fig.…”
Section: Pascmentioning
confidence: 99%
“…Since the lipid phase transition influences the surface potential of the liposome reflecting a sharp change in the ZP during the transition, it was proposed as a screening method for transition temperatures in complex systems, given its high sensitivity and small amount of sample required, that is, 70% less than that required in the use of conventional calorimeters. Many experimental studies dependent on temperature have been reported for lipid systems but predicting mathematical model for the phase behavior was absent [11][12][13].…”
Section: Introductionmentioning
confidence: 99%